Clinical end points in baroreflex activation therapy: what do we need to know?. (June 2013) - de Leeuw, Peter W; Kroon, Abraham A
Many studies have shown that the sympathetic nervous system plays an important part in blood pressure regulation. One of its components is the baroreceptor reflex, which buffers sudden and also potentially chronic changes in blood pressure. The carotid baroreceptors have become a new target in the treatment of hypertensive patients in whom optimal antihypertensive medication fails to normalize the pressure. By electrically stimulating the baroreceptor area, it is now possible to substantially reduce blood pressure in such patients and the effect is well maintained over a prolonged period of time. The hypotensive response is associated with a fall in muscle sympathetic nerve activity, which lends support to the view that baropacing suppresses overall sympathetic outflow from the brain. The procedure appears to be safe and well tolerated. Nevertheless, the authors still need definite proof from prognostic trials that baropacing is superior to intensified medical treatment.